Risk stratification of Barrett's oesophagus using a non-endoscopic sampling method coupled with a biomarker panel: a cohort study. (January 2017) - Ross-Innes, Caryn S; Chettouh, Hamza; Achilleos, Achilleas; Galeano-Dalmau, Nuria; Debiram-Beecham, Irene; MacRae, Shona; Fessas, Petros; Walker, Elaine; Varghese, Sibu; Evan, Theodore; Lao-Sirieix, Pierre S; O'Donovan, Maria; et al.
Summary: Background: Barrett's oesophagus predisposes to adenocarcinoma. However, most patients with Barrett's oesophagus will not progress and endoscopic surveillance is invasive, expensive, and fraught by issues of sampling bias and the subjective assessment of dysplasia. We investigated whether a non-endoscopic device, the Cytosponge, could be coupled with clinical and molecular biomarkers to identify a group of patients with low risk of progression suitable for non-endoscopic follow-up. Methods: In this multicentre cohort study (BEST2), patients with Barrett's oesophagus underwent the Cytosponge test before their surveillance endoscopy. We collected clinical and demographic data and tested Cytosponge samples for a molecular biomarker panel including three protein biomarkers (P53, c-Myc, and Aurora kinase A), two methylation markers ( MYOD1 and RUNX3 ), glandular atypia, and TP53 mutation status. We used a multivariable logistic regression model to compute the conditional probability of dysplasia status. We selected a simple model with high classification accuracy and applied it to an independent validation cohort. The BEST2 study is registered with ISRCTN, number 12730505. Findings: The discovery cohort consisted of 468 patients with Barrett's oesophagus and intestinal metaplasia. Of these, 376 had no dysplasia and 92 had high-grade dysplasia or intramucosal adenocarcinoma. In the discovery cohort, a model with high classification accuracy consisted of glandular atypia, P53 abnormality, and Aurora kinase A positivity, and the interaction of age, waist-to-hip ratio, and length of the Barrett's oesophagus segment. 162 (35%) of 468 of patients fell into the low-risk category and the probability of being a true non-dysplastic patient was 100% (99% CI 96–100) and the probability of having high-grade dysplasia or intramucosal adenocarcinoma was 0% (0–4). 238 (51%) of participants were classified as of moderate risk; the probability of having high-grade dysplasia was 14% (9–21). 58 (12%) of participants were classified as high-risk; the probability of having non-dysplastic endoscopic biopsies was 13% (5–27), whereas the probability of having high-grade dysplasia or intramucosal adenocarcinoma was 87% (73–95). In the validation cohort (65 patients), 51 were non-dysplastic and 14 had high-grade dysplasia. In this cohort, 25 (38%) of 65 patients were classified as being low-risk, and the probability of being non-dysplastic was 96·0% (99% CI 73·80–99·99). The moderate-risk group comprised 27 non-dysplastic and eight high-grade dysplasia cases, whereas the high-risk group (8% of the cohort) had no non-dysplastic cases and five patients with high-grade dysplasia. Interpretation: A combination of biomarker assays from a single Cytosponge sample can be used to determine a group of patients at low risk of progression, for whom endoscopy could be avoided. This strategy could help to avoid overdiagnosis and overtreatment in patients with Barrett's oesophagus. Funding: Cancer Research UK.